Translation and validation of the maternal fetal attachment scale in bahasa Indonesia version - Supriatin Supriatin; Regidor III Dioso; Datin Dr. Hafizah Che Hassan (Faculty of Nursing Universitas Padjadjaran, 2026)
Background: Maternal–fetal attachment (MFA) refers to the emotional bond between a pregnant woman and her unborn child, influencing maternal behaviors and fetal outcomes. The Maternal Fetal Attachment Scale (MFAS) is widely used to assess MFA; however, cultural adaptation is necessary to ensure its validity across different populations. Objective: This study aimed to translate, culturally adapt, and validate the MFAS for use in Bahasa Indonesia with adequate psychometric properties. Methods: A cross-sectional study was conducted among 250 pregnant women attending antenatal clinics in West Java, Indonesia. The MFAS was translated following Beaton et al.’s cross-cultural adaptation guidelines. Content validity was evaluated using the Content Validity Index (CVI) and expert review. Construct validity was assessed through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability was examined using Cronbach’s alpha and the Intraclass Correlation Coefficient (ICC). Results: The Bahasa Indonesia MFAS showed excellent content validity (S-CVI = 1.00). EFA revealed a unidimensional structure explaining 40.76% of the variance, with factor loadings ranging from 0.43 to 0.88. CFA demonstrated good model fit (CFI > 0.90; RMSEA ≤ 0.08). The scale showed high internal consistency (Cronbach’s alpha = 0.899) and good test–retest reliability (ICC = 0.779). Conclusion: The Bahasa Indonesia version of the MFAS is a valid and reliable instrument for assessing maternal–fetal attachment and can be effectively used in maternal health research and clinical practice.